2011
DOI: 10.1002/pro.652
|View full text |Cite
|
Sign up to set email alerts
|

Probing the interactions of an acyl carrier protein domain from the 6‐deoxyerythronolide B synthase

Abstract: The assembly-line architecture of polyketide synthases (PKSs) provides an opportunity to rationally reprogram polyketide biosynthetic pathways to produce novel antibiotics. A fundamental challenge toward this goal is to identify the factors that control the unidirectional channeling of reactive biosynthetic intermediates through these enzymatic assembly lines. Within the catalytic cycle of every PKS module, the acyl carrier protein (ACP) first collaborates with the ketosynthase (KS) domain of the paired subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 32 publications
1
59
0
8
Order By: Relevance
“…The ACP4 interacts with KS5-AT5 linker mainly by electrostatic interaction between E23 on ACP4 helix I and R551 on KS5-AT5 linker. This proposed interaction site between ACP n-1 and KS n is supported by the NMR titration experiments using labeled ACP2 and unlabeled KS3-AT3, in which 1 H- 15 N HSQC signals for some residues in helix I disappeared in the presence of the KS3-AT3 didomain (Charkoudian et al, 2011). …”
Section: Protein-protein Interactions Involving Acpmentioning
confidence: 83%
“…The ACP4 interacts with KS5-AT5 linker mainly by electrostatic interaction between E23 on ACP4 helix I and R551 on KS5-AT5 linker. This proposed interaction site between ACP n-1 and KS n is supported by the NMR titration experiments using labeled ACP2 and unlabeled KS3-AT3, in which 1 H- 15 N HSQC signals for some residues in helix I disappeared in the presence of the KS3-AT3 didomain (Charkoudian et al, 2011). …”
Section: Protein-protein Interactions Involving Acpmentioning
confidence: 83%
“…[12,[18][19][20] Interestingly,h owever,t he selectivity observed for the desired transformation is heavily dependento nt he reaction temperature (Figure1). This reaction, beside ab road substrate scope, features good solvent compatibility.…”
Section: Radical Trifluoromethylation:pathway Ibmentioning
confidence: 99%
“…[17] Indeed, reagents such as 1 are well suited for late-stage trifluoromethylation reactions,i np articular of thiols. [20] Although the chemistry of iodanes is well established,o nly recent computational studies revealed the mechanistic versatility of l 3 -iodanes, reminiscent of that of transition metals. [20] Although the chemistry of iodanes is well established,o nly recent computational studies revealed the mechanistic versatility of l 3 -iodanes, reminiscent of that of transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…Trifluoromethylation reagents based on hypervalent iodine ( 1 and 2 , Figure ) are known to transfer the trifluoromethyl group to various S‐, P‐, O‐, N‐, and C‐nucleophilic functionalities . Thiols, in particular, exhibit excellent reactivity and selectivity in such fluoroalkylation reactions, which has been demonstrated by selective S‐trifluoromethylation of, for example, coenzyme A and Sandostatin using 1 and 2 .…”
Section: Figurementioning
confidence: 99%